Surgical Alloplastic Approach with Dual Mesh in a Multisacular, Recurrent Incisional Hernia – Case Presentation - DANIEL MIHALACHE; BOGDAN SOCEA; ALEXANDRU SMARANDA; ANCA NICA; OVIDIU GABRIEL BRATU; ALEXANDU CONSTANTIN CARAP; CEZAR MOCULESCU; DUMITRU CRISTINEL BADIU; DAN NICOLAE PADURARU; MIHAI DIMITRIU; VLAD DENIS CONSTANTIN (Modern Medicine, 2019)
Repairing an incisional ventral hernia represents a challenge for the surgeon. The high recurrence rates observed during hernia repair by tissue approximation leads to development of tension-free procedures by using prosthetic materials. Incisional or ventral hernia is a very common multifactorial pathology that requires surgical intervention to prevent complications, such as pain, discomfort, bowel obstruction or strangulation. To perform the wall repair it is of utmost importance to understand the pathogenesis of the hernia, the anatomy and physiology of the abdominal wall, and surgical techniques. Several repair methods are available, including open suture repair, open mesh repair, the component separation technique, and tissue expansion assisted closure. To perform the ventral hernia repair properly, a full understanding and correct selection of mesh and management of probable complications, such as seroma, bowel injury, enteric fi stulae, and recurrence, is essential. There are lots of scientific debates about an ideal material for mesh parietal repair. In latest years, the tendency is that the continuous decreasing territory of polyester mesh to be slowly replaced by the increasing territory of polypropylene mesh in open procedures for abdominal incisional hernia repair. The goals of incisional hernia repair are the prevention of visceral eventration, incorporation of the abdominal wall in the repair, provision of dynamic muscular support, and restoration of abdominal wall continuity in a tension-free manner. We present the case of a 55 years old woman who had a history of multiple surgical interventions. We performed an open surgical approach, tension free technique using an intraperitoneal dual-mesh.